In situ forming hydrogels of hyaluronic acid and inulin derivatives for cartilage regeneration. (20th May 2015) - Palumbo, Fabio S.; Fiorica, Calogero; Di Stefano, Mauro; Pitarresi, Giovanna; Gulino, Alessandro; Agnello, Stefano; Giammona, Gaetano
Highlights: Gel forming hydrogels are designed by exploiting an azo-Michael reaction. Hydrogels of HA bearing NH2 or NH2 /C18 with INU-divynilsulfone are prepared. HA with NH2 /C18 improves resistance to HAase hydrolysis and elasticity. High cell growth ratio occurs for NH2 /C18 bearing hydrogel. Abstract: An in situ forming hydrogel obtained by crosslinking of amino functionalized hyaluronic acid derivatives with divinylsulfone functionalized inulin (INU-DV) has been here designed and characterized. In particular two hyaluronic acid derivatives bearing respectively a pendant ethylenediamino (EDA) portion (HA-EDA) and both EDA and octadecyl pendant groups (HA-EDA-C18 ) were crosslinked through an azo-Michael reaction with INU-DV. Gelation time and consumption of DV portions have been evaluated on hydrogel obtained using HA-EDA and HA-EDA-C18 derivatives with a concentration of 3% w/v and a ratio 80/20 w/w respect to the crosslinker INU-DV. The presence of pendant C18 chains improves mechanical performances of hydrogels and decreases the susceptibility to hyaluronidase hydrolysis. Bovine chondrocytes, encapsulated during crosslinking, sufficiently survive and efficiently proliferate until 28 days of analysis.